Public parks in São Paulo: an esthetic adventure in a city without horizon - Vecchiatti, Karin (2019)
A research on the relationships between body and landscape in public parks of São Paulo —an extended analysis of the media approach to these green areas— leads us to consider somatic learning (i.e. how the body learns and acts) as a way to create meaning and experience in big cities. Taking this learning into account seems to be of fundamental importance in recent years: a city that restricts the possibilities of face to face encounters and the learning possibilities in the interaction between bodies and between bodies and landscapes is a city whose destiny is the hardening and failure as a place of well-being. When the ways of living in the city are revealed in everyday activities developed in open green areas and said ways of living are partly linked to the role played by the media, the role of public spaces as city-living laboratories is revealed, and the means and strategies for the management and possible confrontation of the public space crisis in the city are identified. It is in the public and open areas that the chances of creating a more inclusive city are found, where horizontality, collective socializing and respect for diversity can (perhaps) overcome the rigid structures of vertical and exclusive development.